A Polymerized‐Ionic‐Liquid‐Based Polymer Electrolyte with High Oxidative Stability for 4 and 5 V Class Solid‐State Lithium Metal Batteries. Issue 27 (22nd April 2022) - Fu, Chengyin; Homann, Gerrit; Grissa, Rabeb; Rentsch, Daniel; Zhao, Wengao; Gouveia, Tom; Falgayrat, Anaïs; Lin, Rongying; Fantini, Sébastien; Battaglia, Corsin
Abstract: Polymer solid electrolytes for solid‐state batteries typically suffer from low ionic conductivity and low oxidative stability. Herein, a polymer electrolyte based on a polymerized ionic liquid and an ionic liquid plasticizer offering simultaneously a high room‐temperature ionic conductivity of 0.8 mS cm −1 and a high oxidative stability >5.0 V versus Li + /Li, is reported. The electrolyte is compatible with lithium metal and non‐flammable upon direct flame exposure. In symmetric lithium metal cells, the electrolyte enables stable lithium plating and stripping at 0.1 mA cm −2 with a capacity of 1 mAh cm −2 per half cycle for over 1700 h at 25 °C. Cells with a lithium metal anode cycled against a state‐of‐the‐art high‐energy uncoated layered LiNi0.8 Mn0.1 Co0.1 O2 cathode achieve an initial capacity of 162 mA h g −1 and a capacity retention of 72% after 600 cycles to an upper cut‐off voltage of 4.4 V at 25 °C. Cells with a high‐voltage spinel LiMn1.5 Ni0.5 O4 cathode reach an initial capacity of 132 mAh g −1 and a capacity retention of 76% after 300 cycles to an upper cut‐off voltage of 5 V at 25 °C, confirming the high oxidative stability and technological potential of this electrolyte for high‐voltage solid‐state lithium metal batteries. Abstract : A non‐flammable polymer solid electrolyte based on a low‐cost polymerized ionic liquid with a high room‐temperature ionic conductivity of 0.8 mS cm −1 and a high oxidative stability >5.0 V versus Li + /Li enables stable cycling of full cells with a lithium metal anode and an uncoated high‐energy LiNi0.8 Mn0.1 Co0.1 O2 or high‐voltage LiMn1.5 Ni0.5 O4 cathode at 25 °C.